Developing Modern JavaScript Frameworks for Building Interactive Single-Page Applications - Mokoginta, Deyidi; Putri, Desfita Eka; Wattimena, Fegie Yoanti (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
The rapid evolution of modern JavaScript frameworks has significantly enhanced the development of interactive and responsive Single-Page Applications (SPAs). This study compares three prominent JavaScript frameworks—Angular, React, and Vue.Js—focusing on their application in SPA development. The research methodology involves a literature review, a comparative analysis of the critical features of each framework, and a practical implementation to assess their performance, usability, and flexibility. The findings reveal that each framework exhibits distinct advantages and limitations that affect their suitability for different project requirements. Angular is characterized by its extensive built-in features and robust architecture, React by its high flexibility and superior performance, and Vue.js by its user-friendly approach and development efficiency. These results offer valuable insights for developers in selecting the most appropriate framework for their specific project needs, ultimately contributing to more efficient and effective web development.